2019
DOI: 10.1016/j.athoracsur.2019.04.099
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Therapy for Node-Positive Esophageal Cancer After Induction and Surgery: A Multisite Study

Abstract: Background. The benefit of adjuvant treatment for esophageal cancer patients with positive lymph nodes after induction therapy and esophagectomy is uncertain. This in-depth multicenter study assessed the benefit of adjuvant therapy in this population.Methods. A retrospective cohort study from 9 institutions included patients who received neoadjuvant treatment, underwent esophagectomy from 2000 to 2014, and had positive lymph nodes on pathology. Factors associated with administration of adjuvant therapy were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 10 publications
0
35
0
1
Order By: Relevance
“…Moreover, it is critical for patients with positive lymph nodes to receive adjuvant treatment. A previous study reported that adjuvant treatment could significantly improve the median OS of patients with lymph node metastasis after surgery (36).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is critical for patients with positive lymph nodes to receive adjuvant treatment. A previous study reported that adjuvant treatment could significantly improve the median OS of patients with lymph node metastasis after surgery (36).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, adjuvant chemotherapy is not supported by level one evidence for patients who undergo neoadjuvant chemoradiation followed by a complete surgical resection with esophagectomy regardless of tumor regression grade or other clinicopathologic features 16 . However, some recent studies have demonstrated improved survival for patients with esophageal cancer who received adjuvant chemotherapy for persistent lymph node disease after trimodality therapy 17–19 . Brescia et al 17 demonstrated that adjuvant chemotherapy improved median overall survival by 6 months (24 months vs. 18 months [ p = .03]) after trimodality therapy in a cohort of 101 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A large cohort study using the National Cancer Database demonstrated that adjuvant chemotherapy after trimodality therapy was associated with a 30% lower risk of death among esophageal carcinoma patients with residual nodal disease 18 . In addition, a multisite retrospective cohort study demonstrated that patients who received adjuvant chemotherapy after trimodality therapy had longer (2.6 years vs. 2.3 years [ p = .020]) median OS 19 . Clearly, there is a need for more effective systemic therapies for high‐risk patients who have completed trimodality therapy of locally advanced esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients included in the aforementioned studies did not receive preoperative chemoradiotherapy. The lower likelihood of completing adjuvant treatment following pretreatment prior to surgery has been reported [ 17 ]. This is supported by the low completion rates of postoperative treatment (42–50%) achieved in studies with gastroesophageal cancer patients assigned to both pre- and postoperative treatment, which are in line with our completion rate [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%